Antiepileptogenic Effect of Subchronic Palmitoylethanolamide Treatment in a Mouse Model of Acute Epilepsy - Post, Julia M.; Loch, Sebastian; Lerner, Raissa; Remmers, Floortje; Lomazzo, Ermelinda; Lutz, Beat; Bindila, Laura (Frontiers in Molecular Neuroscience, 2018)
Research on the antiepileptic effects of (endo-)cannabinoids has remarkably progressed in the years following the discovery of fundamental role of the endocannabinoid system in controlling neural excitability. Moreover, an increasing number of well-documented cases of epilepsy patients exhibiting multi-drug resistance report beneficial effects of cannabis use. Pre-clinical and clinical research has increasingly focused on the antiepileptic effectiveness of exogenous administration of cannabinoids and/or pharmacologically induced increase of endocannabinoids (eCBs) such as anandamide (AEA). Concomitant research has uncovered the contribution of neuroinflammatory processes and peripheral immunity to the onset and progression of epilepsy. Accordingly, modulation of inflammatory pathways such as cyclooxygenase-2 (COX-2) was pursued as alternative therapeutic strategies in epilepsy. Palmitoylethanolamide (PEA) is an endogenous fatty acid amide related to the centrally and peripherally present endocannabinoid anandamide, and is a naturally occurring nutrient that has long been recognized for its analgesic and anti-inflammatory properties. Neuroprotective and anti-hyperalgesic properties of PEA were evidenced in neurodegenerative diseases, and antiepileptic effects in pentylenetetrazol (PTZ), maximal electroshock (MES) and amygdaloid kindling models of epileptic seizures. Moreover, numerous clinical trials in chronic pain revealed that PEA-treatment is devoid of addiction potential, dose limiting side effects and psychoactive effects, rendering PEA an appealing candidate as antiepileptic compound or adjuvant. In the present study, we aimed at assessing antiepileptic properties of PEA in a mouse model of acute epileptic seizures induced by systemic administration of kainic acid (KA). KA-induced epilepsy in rodents is assumed to resemble to different extents human temporal lobe epilepsy (TLE) depending on the route of KA administration; intracerebral (i.c.) injection was recently shown to most closely mimic human TLE, while systemic KA-administration causes more widespread pathological damage, both in brain and periphery. To explore the potential of PEA to exert therapeutic effects both in brain and periphery, acute and subchronic administration of PEA by intraperitoneal (i.p.) injection was assessed on mice with systemically administered KA: Specifically, we investigated i) neuroprotective and anticonvulsant properties of acute and subchronic PEA treatment in KA-induced seizure models and ii) temporal dynamic of eCB and eicosanoid (eiC) levels in hippocampus and plasma over 180 min post seizure induction in